Study of the cancer incidence in kids and juveniles in Yerevan in relation to air and soil pollution on their dwelling sites - H. S. Movsesyan; R. M. Aroutounian; L. V. Sahakyan; Sh. G. Asmaryan; H. M. Galstyan; G. K. Bazikyan; H. A. Martirosyan; A. K. Saghatelyan (ՀՀ ԳԱԱ հրատ.)
The article covers a study of correlation between cancer incidence in children and juveniles and indices of air pollution as well as levels of heavy metal pollution of the territory of the Yerevan. Ուսումնասիրված է հնարավոր համահարաբերակցական կապը երեխաների և երիտասարդների օնկոլոգիական հիվանդությունների բժշկական ցուցանիշների և ծանր մետաղներով Երևանի տարածքի աղտոտման մակարդակի, ինչպես նաև օդի աղտոտման ցուցանիշների միջև: Изучена корреляционная связь между показателями онкологических заболеваний у детей и молодых людей и уровнем загрязнения воздуха, а также территории Еревана, в том числе, тяжелыми металлами.
Keywords: Biology; Genetics